True and intentionally fabricated memories. Issue 6 (June 2013) - Justice, Lucy V.; Morrison, Catriona M.; Conway, Martin A.
The aim of the experiment reported here was to investigate the processes underlying the construction of truthful and deliberately fabricated memories. Properties of memories created to be intentionally false (fabricated memories) were compared to properties of memories believed to be true (true memories). Participants recalled and then wrote or spoke true memories and fabricated memories of everyday events. It was found that true memories were reliably more vivid than fabricated memories and were nearly always recalled from a first-person perspective. In contrast, fabricated differed from true memories in that they were judged to be reliably older, were more frequently recalled from a third-person perspective, and linguistic analysis revealed that they required more cognitive effort to generate. No notable differences were found across modality of reporting. Finally, it was found that intentionally fabricated memories were created by recalling and then "editing" true memories. Overall, these findings show that true and fabricated memories systematically differ, despite the fact that both are based on true memories.